Identification of New College Students' Problems in Riverbank - Makaria, Eklys Cheseda; Sari, Nina Permata (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2022)
The city of Banjarmasin is one of the riverbank areas, which every year accepts new college students from various regions every day. Adjustment to the new learning environment and system creates problems for new college students. This study describes the problems new college students face from the class of 2021 at Lambung Mangkurat University. This research was conducted using mixed methods with an explanatory sequential design. The research sample was selected by purposive sampling technique. Quantitative data was collected using DCM, and qualitative data were obtained using counseling interviews. Quantitative data shows that in group analysis, new college students face problems in personal 44.9%, social 59.5%, career 59.5%, and academic 60.3%. Qualitative data collected using counseling showed that these students experienced personal and social problems. The social issues are 1) difficulty managing time; (2) lack of confidence; (3) harboring issues on their own, so they get stressed quickly, (4) overthinking, (5) relationships with parents that are not good; (6) unhealthy friendships or toxic relationship; (7) there is a misunderstanding with peers; and (8) difficulty adapting to the class schedule and new environment. Problems in these two fields have an impact on the academic field, making students less motivated to learn because of the mismatch between the desires and the majors studied, difficulty dividing time, and difficulty adapting to a new environment, coupled with problems that make new students feel stressed and depressed with their study activities